2004
DOI: 10.1186/1471-2105-5-202
|View full text |Cite
|
Sign up to set email alerts
|

Identifying spatially similar gene expression patterns in early stage fruit fly embryo images: binary feature versus invariant moment digital representations

Abstract: Background: Modern developmental biology relies heavily on the analysis of embryonic gene expression patterns. Investigators manually inspect hundreds or thousands of expression patterns to identify those that are spatially similar and to ultimately infer potential gene interactions. However, the rapid accumulation of gene expression pattern data over the last two decades, facilitated by high-throughput techniques, has produced a need for the development of efficient approaches for direct comparison of images,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…In this case, the similarity score ( S ) between two images ( Q and D ) is given by S QD = | Q ∩ D |/| Q ∪ D |, where | Q ∩ D | is the size of the intersection of expression (count of black pixels) between images Q and D and | Q ∪ D| is the size of the union between images Q and D . We have previously shown that this approach emphasizes spatial overlap, which is biologically more meaningful than shape matching and invariant moment based features (Kumar et al, 2002; Gurunathan et al, 2004). We have also found that it performs with an effectiveness similar to the computationally more intensive Gaussian Mixture Model method (Peng et al, 2007), which in our hands is very sensitive to shifts in image properties, such as the color and contrast (Gargesha et al, 2008; Gargesha et al, 2009a; Gargesha et al, 2009b; Roy et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this case, the similarity score ( S ) between two images ( Q and D ) is given by S QD = | Q ∩ D |/| Q ∪ D |, where | Q ∩ D | is the size of the intersection of expression (count of black pixels) between images Q and D and | Q ∪ D| is the size of the union between images Q and D . We have previously shown that this approach emphasizes spatial overlap, which is biologically more meaningful than shape matching and invariant moment based features (Kumar et al, 2002; Gurunathan et al, 2004). We have also found that it performs with an effectiveness similar to the computationally more intensive Gaussian Mixture Model method (Peng et al, 2007), which in our hands is very sensitive to shifts in image properties, such as the color and contrast (Gargesha et al, 2008; Gargesha et al, 2009a; Gargesha et al, 2009b; Roy et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…A common first step in discovering gene interactions is to identify genes with overlapping expression patterns. However, the standard practice of manual inspection of images is not efficient given the extraordinary number of images available today (Gurunathan et al, 2004; Peng et al, 2007; Walter et al, 2010). This problem has been addressed utilizing textual descriptions of gene expression images employing controlled vocabularies (CVs; Janning, 1997; Brody, 1999; FlyBase, 1999; Drysdale, 2001; Tomancak et al, 2002; Matthews et al, 2005; Grumbling and Strelets, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Black-and-white spatial profiles (representing gene expression in the developing embryo) were created for each image. The black-and-white spatial profiles translate into Binary Feature Vectors representing the composite spatial expression of each gene or genomic element ( Gurunathan et al , 2004 ). Images were annotated by genotype, image source, Campos-Ortega stage ( Campos-Ortega and Hartenstein, 1985 ), and anatomical orientation.…”
Section: Methodsmentioning
confidence: 99%